Social environment and physical activity of adolescents in Greece - Agkopian, Ioannis (2019)
Physical activity (PA) is of crucial importance for the health and well being of human beings. It is influenced by various factors, which are interconnected and thus renders it a complex subject to study. The aim of this study is to describe the PA in Greece and Finland especially the social environment of PA currently and in the past as well as the Greek social environment and its contribution to the PA results. One of the factors exerting influence on PA is the social environment especially during the adolescent years. Having the social environment as an angle of approach, this study aims to understand why Greece is one of the least physically active countries in Europe and what the major differences of the social environment are when placed next to one of the most physically active countries (Finland). The design of this research is theoretical and is based on previously conducted international studies and surveys on PA, such as the Eurobarometer, international studies on the social determinants of health and wellbeing, as well as studies focusing on the social environment (HBSC studies). The analysis took place according to thematic content analysis method proposed by Mayring (Philipp, 2014). In order to narrow the broad term of the social environment down, it is defined in this research as family, peers and media. The Greek adolescents grow up in a social environment, which is much more conservative and strict than many of their Finnish peers. Not being able to spend much time with their peers outside school until they reach a certain age can be a barrier to their development. The high bullying rate in Greece is a statement of the xenophobia and uncertainty still lingering within the Greek society. Possible reasons for this type of behavior can be traced in the harsh past of Greece which brought certain ideology to the surface as means of survival. Greece is also one of the countries where adolescents spend most of their time watching television and having electronic media contact with their peers. These notions however, are still prominent in modern society influencing the social environment and in turn the PA levels. It seems that sport and PA have different meanings in the Greek and Finnish society. The Finnish society approaches sport with a broadened perspective as opposed to Greece. Keywords: Physical activity, social environment, adolescents, Greece, culture, Finland